Determinants of market share in sharia banking of the ASEAN countries - Andi Ayu Frihatni; Ahmad Dzul Ilmi; Putri Aulia Rustan (Indonesian Journal of Islamic Economics Research, 2023)
This study analyzes the effect of Islamic banks on economic growth in ASEAN. This type of research is quantitative, with data analysis using multiple linear regression and classical assumption tests. The research sample is Islamic banking registered with World Bank ASEAN. The findings of this study consist of 1) competitiveness, capitalization, financing risk, size, and interest rates do not affect market share. 2) GDP and exchange rate effect on market share. The results of this study are expected to create an integrated and robust Islamic financial area, so there needs to be cooperation among relevant parties among ASEAN countries to reduce the gap. Sharia economic actors and practitioners must remain enthusiastic and optimistic in Sharia society and socialize Sharia. The benchmark of competitive advantage is internal strength that is better than its competitors, and the company can fix internal weaknesses. In addition, external factors also need attention, and companies must be observant to see existing opportunities and minimize threats.